Analysis Of Risk Factors For Adolescent Pregnancy And Innovations In Community-Based Prevention Interventions In Rural Areas - Benedika Mardewi Iswari; Lidia Hastuti; Lilis Lestari; Suriadi Jais; Haryanto Haryanto (CV. AFDIFAL MAJU BERKAH, 2026)
Teenage pregnancy in rural areas remains a complex health and social issue in Indonesia and Southeast Asia. Low reproductive health literacy, poverty, and conservative cultural norms contribute to the high pregnancy rate in the 15–19 age group. This study aims to review various factors influencing teenage pregnancy in rural areas and identify innovative community-based preventive interventions that have been implemented. This research is part of a scoping study framework using the Systematic Literature Review (SLR) approach guided by PRISMA 2020. The literature search was conducted in PubMed, CINAHL, and Scopus databases using a combination of keywords in Indonesian and English. Of the 143 articles identified, 12 met the inclusion criteria and were analyzed using the thematic analysis approach of Braun and Clarke (2006). The results of the study indicate that the involvement of families, community leaders, and educational institutions plays a crucial role in increasing adolescent reproductive awareness. Participatory community-based interventions based on local values ​​are considered more effective than top-down approaches. A collaborative, cross-sectoral approach is a promising strategy for reducing teenage pregnancy rates in rural areas.